Knowledge, attitudes and practices of dengue prevention between dengue sustained hotspots and non-sustained hotspots in Singapore: a cross-sectional study - Jeth WeiQuan Chng; Tamilsalvan Parvathi; Junxiong Pang (Scientific Reports, 2022)
Abstract Dengue sustained hotspots (SHS) have resulted in a significant public health burden. In our study, we aimed to (1) compare knowledge, attitudes and practices (KAP) scores between SHS and non-sustained hotspots (NSHS); and (2) identify and describe gaps and factors associated with KAP of dengue prevention among SHS residents residing in Singapore. A cross-sectional study with convenience sampling was conducted using digital survey in randomly selected SHS and NSHS residential areas, consisting of residents aged 21 or older and who had been residing in their existing housing unit in 2019 and 2020. Chi-square test and T-test were used for comparison analysis of categorical and continuous variables, respectively. A total of 466 respondents completed the self-administered, anonymous survey. There were no significant difference in mean scores for Knowledge [SHS(24.66) vs. NSHS(24.37); P: 0.18], Attitudes [SHS(10.38) vs NSHS(10.16); P: 0.08] and Practices [SHS(9.27) vs NSHS(8.80); P: 0.16] sections. Significant SHS-associated factors identified were age group 41–50 years old [95%CI: 1.25–5.03], Malay (95%CI: 0.17–0.98), up to secondary school education (95%CI: 0.07–0.65), private condominium (95%CI: 1.17–3.39), residing in same household unit for 2–5 years (95%CI: 2.44–6.88), respondents who know that mosquito can breed in open container with stagnant water (95%CI: 0.06–0.98), disagree that reducing Aedes mosquitoes is the only way to prevent dengue: (95%CI: 1.19–3.00) and go to clinic/hospital even without severe symptoms: (95%CI: 0.39–0.95). These independent factors associated with dengue sustained hotspots may influence the risk of dengue transmission in residential areas.